O debate modernidade / pós-modernidade e a crise socioambiental: um estudo sobre teses e dissertações brasileiras em educação ambiental - Zupelari, Maria Fernanda Zanatta [UNESP] (2014)
Assuming that academic research on environmental education often cites and criticizes some characteristics of Modernity and Modern Science, as the factors that deepen the environmental crisis: namely, reductionism and fragmentation of science and modern education; capitalist mode-of-production and its accumulator principle; the dichotomous relationship between nature and society or between subject and object, it becomes important to identify and analyze the relations between the debate Modernity / Post-Modernity and the environmental crisis expressed in theses and dissertations on Brazilian Environmental Education Research. Research on the fundamentals of environmental education is important to clarify, within its possibilities, the complex relationships between society and nature and the environmental crisis, as well as contribute to the epistemological improvement. Therefore, we seek to identify which aspects of this debate, which authors and which concepts or categories are privileged in these surveys. Thus, a cut was held from selected studies analyzed of the theses’s Bank Project “analysis of academic production (theses and dissertations) Environmental Education in Brazil. A total of twenty-four selected documents, which constitute the documentary corpus are eighteen dissertations and six doctoral theses. These works were defended between 1992 and 2009, and there is little concentration in the period 2006-2009. Theses and dissertations were defended in nineteen different institutions, highlighting USP (there were four defended works). 54.1% of the total of selected studies are located in the Southeast, 33% in the South, 8% in the Midwest region, and finally, 4% in the Northern region. There are no works developed in northeastern Brazil among the constituents work this documentary corpus. Nineteen of the selected research were produced by public institutions, three confessional institutions, and two in private institution. About...